Movement, Crisis, and (Be)longing: Affect and Migrant Identity in Agnieszka Dale’s Short Stories - Cieplińska, Katarzyna (Slavia Centralis, 2026)
This article examines how migrant belonging is regulated affectively before it becomes a matter of legal exclusion in Agnieszka Dale’s short stories Fox Season, A Happy Nation, and What We Should Feel Now. Rather than depicting spectacular moments of crisis, Dale’s narratives trace the quiet restructuring of domestic intimacy under the emotional pressure of pre-Brexit Britain. I argue that Dale uses childhood, household routines, and everyday gestures to reveal how migrants internalise surveillance at the level of affect. Drawing selectively on Sara Ahmed’s theory of emotional circulation, Lauren Berlant’s concept of intimate publics, and Judith Butler’s reflections on precarity, the article demonstrates that belonging in these stories emerges as anticipatory emotional labour rather than stable social recognition. By placing Dale in dialogue with Central/Eastern European discussions, the article situates her prose within a broader literary exploration of crisis as an affective condition.